The Utilization of Picture Storybook: Can It Increase Students' Critical and Creative Thinking Skills? - Rindengan, Mersty (Jurnal Prima Edukasia, 2023)
Learning media play an essential role in the development of students' skills. However, the use of learning media remains low, particularly in developing students' critical and creative thinking skills. This study aims to analyze the increase in critical and creative thinking skills of fifth-grade students in participating in learning using the picture storybook learning media. This study was quasi-experimental and utilized pre- and post-test designs. The subjects of this study were 50 students of a fifth-grade elementary school in cluster IV of Sintang District. The research sample was taken using a purposive sampling technique. The research instrument used was a test instrument to measure students' critical and creative thinking skills. Research data were analyzed using statistical tests, namely the MANOVA test and the independent sample t-test. The results of this study indicate a significant increase in students who learn by utilizing picture storybook learning media in terms of critical and creative thinking skills.